Percent body fat, but not lean mass, is associated with objectively measured physical function in middle-aged women. (December 2020) - Ward-Ritacco, Christie L.; Meyer, Ashley; Walker, Grace; Riebe, Deborah; Sabik, Natalie J.
Highlights: In this study of middle-aged women, steps per day rather than minutes of moderate to vigorous physical activity were more strongly associated with measures of objective physical function. Adiposity, but not lean mass, was significantly associated with objectively measured physical function in middle-aged women. Measures of objective physical function included a seated transfer task, 30 second chair stand, a six-minute walk task, 8-foot timed up and go, and a lift and carry task. Abstract: Objectives: The relationship between components of body composition and physical function is not well characterized among middle-aged women. This cross-sectional study examined the strength of the associations between lean mass and percent fat and physical function in middle-aged women. Study Design: Body composition, physical function and physical activity were objectively measured in 80 women (mean age 52.58 ± 6.10 years; range = 40−63 years). Main Outcome Measures: Adiposity (%Fat) and lean mass were measured via dual-energy x-ray absorptiometry. Steps/day and minutes of low-, moderate- and vigorous-intensity physical activity were assessed via accelerometer. Physical function was measured via a seated transfer task, 30-second chair stand, a six-minute walk task, 8-foot timed up and go, and a lift and carry task. Results : When controlling for steps/day, measures of lean mass were related to performance on the seated transfer task (r = .25) and 30-second chair stand (−.26) (both p > 0.05), while %Fat was related to performance on the seated transfer task ( r = .53), 8-foot timed up and go (r = .32), 30-second chair stand ( r = −.35), and six-minute walk ( r = −.48; all p ≤ 0.05). Linear regression analyses revealed: (1) age, steps/day, and %Fat were independently related to performance on the seated transfer task and 30-second chair stand (both p ≤ 0.05), (2) %Fat was associated with six-minute walk and 8-foot up-and-go performance ( p ≤ 0.01); none of the variables included were associated with lift and carry. Conclusions: Adiposity but not lean mass was associated with objectively measured physical function in middle-aged women. Interventions that focus on reducing body fat may be an effective method for improving functional performance among women in this age group.